2006
DOI: 10.1111/j.1460-9568.2006.05148.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of brain neurons expressing the dopamine D4 receptor gene using BAC transgenic mice

Abstract: The dopamine D4 receptor (D4R) has received considerable interest because of its higher affinity for atypical antipsychotics, the extremely polymorphic nature of the human gene and the genetic association with attention deficit and hyperactivity disorder (ADHD). Several efforts have been undertaken to determine the D4R expression pattern in the brain using immunohistochemistry, binding autoradiography and in situ hybridization, but the overall published results present large discrepancies. Here, we have explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 37 publications
6
84
1
1
Order By: Relevance
“…The NAc has projections from similar areas, such as infralimbic and cingulate areas, but there is an increasing amount of projections from the hippocampus, entorhinal cortex, piriform cortex, amygdala, and subiculum (McGeorge and Faull, 1989). There is indication that these areas projecting to the NAc may have lower amounts of DRD4 influence (as compared with striatal projections) and, therefore, may not be as affected by loss of the DRD4, which may explain why we see data trends (Noain et al, 2006). Also, Rivera et al (2002) reported higher local expression of DRD4 in the Str in comparison with the NAc of rats, but the presence of DRD4 in these areas is debated (Noain et al, 2006).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The NAc has projections from similar areas, such as infralimbic and cingulate areas, but there is an increasing amount of projections from the hippocampus, entorhinal cortex, piriform cortex, amygdala, and subiculum (McGeorge and Faull, 1989). There is indication that these areas projecting to the NAc may have lower amounts of DRD4 influence (as compared with striatal projections) and, therefore, may not be as affected by loss of the DRD4, which may explain why we see data trends (Noain et al, 2006). Also, Rivera et al (2002) reported higher local expression of DRD4 in the Str in comparison with the NAc of rats, but the presence of DRD4 in these areas is debated (Noain et al, 2006).…”
Section: Discussionmentioning
confidence: 52%
“…There is indication that these areas projecting to the NAc may have lower amounts of DRD4 influence (as compared with striatal projections) and, therefore, may not be as affected by loss of the DRD4, which may explain why we see data trends (Noain et al, 2006). Also, Rivera et al (2002) reported higher local expression of DRD4 in the Str in comparison with the NAc of rats, but the presence of DRD4 in these areas is debated (Noain et al, 2006). Our recordings were made in the NAc core.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…D4 reseptörleri temel olarak ventral tegmental alan, prefrontal korteks, singulat girus ve insuladan gelen mezokortikal projeksiyonların uyardığı bölgelerde yerleşmiş-tir. [59] DRD-4 7R aleli olan bulimiası olan kadınlarda yaşam boyu artmış beden kitle indeksi riskinin olduğu gösterilmiştir. [60] Bir başka preklinik araştırmada fareler ile yapılan bir deneyde, DAT geninde olan bir bozulmanın sinaptik dopamin artışına ve artmış enerji alımı ile lezzetli yiyeceklerin tüketiminde artışla sonuçlandığı saptanmıştır.…”
Section: Genetik Araştırmalarunclassified
“…It is important to note, however, that D4R mRNA and protein levels are exceedingly low in the hippocampus, and its expression in pyramidal cells and/or interneurons is far from established. [16][17][18] The known spatial distribution of some crucial elements might be helpful, however, in assembling a network model: First, ErbB4 is expressed in numerous GABAergic interneurons across all layers (see below). Second, glutamatergic SC→CA1 synapses are located in the stratum radiatum.…”
Section: Location Location Locationmentioning
confidence: 99%